SEGMENTATION AND TARGET MARKETS FOR ISLAMIC EDUCATION SERVICES - Astuti, Serli Widia; Astri, Astri; Saipulannur, Saipulannur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article discusses market segmentation with several segmentation approaches, namely demographic segmentation, geographic segmentation, psychographic segmentation, psychological segmentation, and benefits segmentation to target outstanding students from various regions. In relation to education, services can be defined as the activities of educational institutions providing services or delivering educational services to consumers in a way that satisfies them. Marketing in the context of educational services is a social and managerial process to obtain what is needed and desired through creating offers, exchanging valuable products with other parties in the educational sector. This paper uses qualitative research methods. Where the preparation produces data in the form of descriptions. The data collection technique used by the author is using literature study or library research. The data collection method can be done by researching books, journals or websites which are definitely related to the material to be discussed.